Renal Allograft Biopsies with Polyomavirus BK Nephropathy: Turin Transplant Center, 2015–19 - Elisa Zanotto; Anna Allesina; Antonella Barreca; Francesca Sidoti; Ester Gallo; Paolo Bottino; Marco Iannaccone; Gabriele Bianco; Luigi Biancone; Rossana Cavallo; Cristina Costa (Viruses, 2020)
Background: In kidney transplant patients, polyomavirus-associated nephropathy (PVAN) represents a serious complication; the key factor for the development of PVAN is immunosuppression level and modulation of anti-rejection treatment represents the first line of intervention. Allograft biopsy and histology remain the criterion standard for diagnosing PVAN. Methods: All consecutive renal biopsies with the diagnosis of PVAN carried out at the University Hospital City of Health and Science of Turin over a five-years period were studied. Renal allograft biopsy was performed due to renal function alterations associated to medium-high polyomavirus BK (BKV)-DNA levels on plasma specimen. Results: A total of 21 patients underwent a first biopsy to diagnose a possible BKV nephropathy, in 18, a second biopsy was made, in eight, a third biopsy, and finally, three underwent the fourth renal biopsy; following the results of each biopsies, immunosuppressant agents dosages were modified in order to reduce the effect of PVAN. Conclusions: In this study, the clinical and histological features of 21 kidney transplant recipients with BKV reactivation and development of PVAN are described. To date, the only treatment for PVAN consists in the reduction of immunosuppressive agents, constantly monitoring viral load.